Evaluation of a Mentoring Program for Beginning Teachers in Terms of the Learning Environment and Student Outcomes in Participants' School Classrooms - Pickett, L.; Fraser, Barry (Nova Publishers, 2009)
The evaluation of teacher professional development programs often involves surveying participant teachers' opinions and satisfaction related to various aspects of a program. But the litmus test of the success of any professional development program is the extent of changes in teaching behaviors and ultimately student outcomes in the participating teachers' school classrooms. Our evaluation of a two-year mentoring program in science for beginning elementary school teachers is unique in that it drew on the field of learning environments in evaluating this program in terms of participants' classroom teaching behavior as assessed by their school students' perceptions of their classroom learning environments. As well, students' attitudes to and achievement in science were assessed. Changes over a school year were monitored. The sample consisted of seven beginning Grade 3-5 teachers in southeastern U.S. and their 573 elementary school students. A modified version of the What ls Happening In this Class? (WIHIC) questionnaire was used to assess student perceptions of classroom learning environment as a pretest and a posttest. Data analyses supported the sound factorial validity of the WIHIC. Use of MANOVA and effect sizes supported the efficacy of the mentoring program in terms of some improvements over time in the classroom learning environment and students' attitudes and achievement.These quantitative data provided a starting point from which qualitative data gathering methods (e.g. interviews and focus groups) were used to gain a more in depth understanding of changes in attitudes among the mentored teachers. The teachers' attitudes were investigated in terms of their level of confidence, knowledge, and valuing of teaching science, active learning in science, positive classroom learning environments, reflective practice, and overall impressions of the mentoring experience.